The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1128/jcm.01590-12
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Dirofilaria Species Causing Human and Canine Infections in Hong Kong

Abstract: Dirofilariasis is globally the commonest manifestation of zoonotic filariasis. We report the detection of a novel canine species causing human and canine dirofilariasis in Hong Kong. Three human cases occurring over 10 months were identified, one presenting with cervical lymphadenopathy, one with an abdominal subcutaneous mass, and one with a subconjunctival nodule. Transected worms recovered from the resected abdominal subcutaneous mass were morphologically compatible with Dirofilaria. The cox1 gene sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
62
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 30 publications
0
62
1
Order By: Relevance
“…4 As a common amphixenosis, this disease is now receiving widespread attention, and increasing numbers of cases have been reported in recent years. [5][6][7][8][9] In some areas, disease is present in up to 30% of human serum samples. 10 Because of the wide epidemic range and multiple hosts, heartworms are now considered to be among the most harmful Dirofilaria nematodes infecting man and other mammals.…”
Section: Introductionmentioning
confidence: 99%
“…4 As a common amphixenosis, this disease is now receiving widespread attention, and increasing numbers of cases have been reported in recent years. [5][6][7][8][9] In some areas, disease is present in up to 30% of human serum samples. 10 Because of the wide epidemic range and multiple hosts, heartworms are now considered to be among the most harmful Dirofilaria nematodes infecting man and other mammals.…”
Section: Introductionmentioning
confidence: 99%
“…PCR products were purified and sequenced as described previously (12). All statistical analyses were performed using PASW Statistics 18 and VassarStats (http://vassarstats.net/).…”
mentioning
confidence: 99%
“…10 In 2012, To et al 11 reported a case series of three patients who had diseases caused by a novel Dirofilaria species in Hong Kong. This species was found in 3% of stray dogs' blood samples in Hong Kong.…”
Section: Discussionmentioning
confidence: 99%